Should heart failure be regarded as a terminal illness requiring palliative care? A study of heart failure patients', carers' and clinicians' understanding of heart failure prognosis and its management. Issue 4 (21st July 2017) - Stocker, Rachel; Close, Helen; Hancock, Helen; Hungin, A Pali S
Abstract : Objectives: Communication and planning for heart failure (HF) care near the end of life is known to be complex. Little is known about how the patient experience of palliative assessment and communication needs change over time, and how this might inform management. Our aim was to explore experiences of giving or receiving a prognosis and advanced palliative care planning (ACP) for those with HF. Methods: We carried out a longitudinal grounded theory study, employing in-depth interviews with 14 clinicians (primary and secondary care) and observations of clinic and home appointments, followed by a series of interviews with 13 patients with HF and 9 carers. Results: Overall, the majority of participants rejected notions of HF as a terminal illness in favour of a focus on day-to-day management and maintenance, despite obvious deterioration in disease stage and needs over time. Clinicians revealed frustration about the uncertain nature of HF prognosis, leading to difficulties in planning. Others highlighted the need to deliver problem-based, individualised care but felt constrained sometimes by the lack of multidisciplinary ACP. Patients reported an absence of prognostic discussions with clinicians. Conclusions: This is the first study exploring the experiences of prognostic communication at all stages of HF. Findings raise questions regarding the pragmatic utility of the concept of HF as a terminal illness and have implications for future HF care pathway development. Findings support the incorporation of a problem-based approach to management, which recognises the importance of everyday functioning for patients and carers as well as the opportunity for ACP.